Enhancing People’s Capabilities and Entitlements in Asia: The Experience of an Export Production Village Project in Sri Lanka - Piyadasa Ratnayake (Hasanuddin University, 2015)
It is common knowledge that most developing countries in Asia have failed to channel the benefits of their rapid economic growth to make any significant progress in the movement of reducing rural poor. This is because the rural sector is isolated from the modern sector or the so-called industrial sector in the national development process. As a result, people in the rural sector do not get equal opportunities to participate in the development process of the modern sector and thereby do not receive growth benefits equally. The present study based on the Export Production Village (EPV) project aims to rectify this weakness to some extent by providing equal opportunities for rural people to participate in modern development activities, while equitably distributing the growth benefits of national development among rural stakeholders. Thus, it aims to enhance people`s capabilities and entitlements, by creating production and marketing linkages between the two sectors. The main aim of the present study is to investigate how far this EPV project is able to improve people`s Capabilities and Entitlements through transferring growth benefits of the modern sector to the rural economy while providing productive opportunities to use their own resource endowments to participate in the national development process.